2010
DOI: 10.1007/s10162-010-0211-x
|View full text |Cite
|
Sign up to set email alerts
|

CD44 is a Marker for the Outer Pillar Cells in the Early Postnatal Mouse Inner Ear

Abstract: Cluster of differentiation antigens (CD proteins) are classically used as immune cell markers. However, their expression within the inner ear is still largely undefined. In this study, we explored the possibility that specific CD proteins might be useful for defining inner ear cell populations. mRNA expression profiling of microdissected auditory and vestibular sensory epithelia revealed 107 CD genes as expressed in the early postnatal mouse inner ear. The expression of 68 CD genes was validated with real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…By E17 (approximately E15.5 in mice), these cells express p75 NTR (von Bartheld et al 1991), although the timing of specificity for inner pillar cells in mice may be somewhat later (Mueller et al 2002;Woods et al 2004). We found that the earliest expression of the only known outer pillar cell marker, CD44 (Hertzano et al 2010), occurred in controls at E17.5, when inner pillar cells, identified by p75 NTR staining, had clearly already differentiated. Since the number of CD44-positive cells increased in Fgfr3 P244R/+ cochlear cross-sections by one at E18.5 and by two at P3 but p75 NTR -positive cells did not change and neither did the number of SOX2-positive support cells, we conclude that Muenke syndrome model cochleae have a cell fate transformation from Deiters' to outer pillar-like cells that occurs over 4-5 d. This fate transformation is likely a direct effect of increased signaling by FGFR3 P244R because Fgfr3 is expressed in developing support cells, and the Deiters' cell region of Fgfr3 P244R/+ cochleae shows ectopic and/or enhanced expression of several FGF target genes.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…By E17 (approximately E15.5 in mice), these cells express p75 NTR (von Bartheld et al 1991), although the timing of specificity for inner pillar cells in mice may be somewhat later (Mueller et al 2002;Woods et al 2004). We found that the earliest expression of the only known outer pillar cell marker, CD44 (Hertzano et al 2010), occurred in controls at E17.5, when inner pillar cells, identified by p75 NTR staining, had clearly already differentiated. Since the number of CD44-positive cells increased in Fgfr3 P244R/+ cochlear cross-sections by one at E18.5 and by two at P3 but p75 NTR -positive cells did not change and neither did the number of SOX2-positive support cells, we conclude that Muenke syndrome model cochleae have a cell fate transformation from Deiters' to outer pillar-like cells that occurs over 4-5 d. This fate transformation is likely a direct effect of increased signaling by FGFR3 P244R because Fgfr3 is expressed in developing support cells, and the Deiters' cell region of Fgfr3 P244R/+ cochleae shows ectopic and/or enhanced expression of several FGF target genes.…”
Section: Discussionmentioning
confidence: 47%
“…1D-K). Outer pillar cells were labeled with antibodies directed against CD44, which is also expressed by a subset of cells in the inner and outer sulci on either side of the sensory epithelium but not by inner pillar cells (Hertzano et al 2010). Sensory hair cell bodies and support cell nuclei were identified using antibodies directed against MYO7A and SOX2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For example, RANTES/CCL1 (Bolin et al, 1998) and tumor necrosis factor (TNF) (Bianchi et al, 2005), as well as the receptors CCR1 (for RANTES) and CXCR4/2 (for MIF) (Bernhagen et al, 2007) and TNFR1/2 (also known as TNFRSF1A/B) (Zou et al, 2005), are found in the inner ear. Another MIF receptor, CD44, is expressed in pillar cells (Hertzano et al, 2010) in developing and adult inner ear tissues. The function of these various cytokines and cytokine-driven signaling systems has yet to be fully explored, and any potential interactions between them still need to be addressed.…”
Section: Research Article Development 139 (24)mentioning
confidence: 99%
“…Similarly, the percentage of vascular endothelial cells in the newborn mouse inner ear following a standard dissection is three fold higher in the vestibular compared with the auditory sensory epithelia . It is therefore not surprising that in our work describing the expression of cluster of differentiation (CD) genes in the mouse inner ear, CD16, CD68, CD163 and CD309 were found to be highly enriched in the vestibular epithelia, since they are all cell surface markers which are expressed on the vascular endothelium or blood vessel lymphocytes (Hertzano et al, 2010). Likewise, the percentage of the hair cells or other cell types out of the total number of cells in a dissected tissue may vary throughout development.…”
Section: Cell Type-specific Gene Expression Analysismentioning
confidence: 93%